2021
DOI: 10.1111/lam.13493
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic application of antibiotics selects extended‐spectrum β‐lactamase and carbapenemases producing Gram‐negative bacteria in the oral cavity

Abstract: Significance and Impact of the Study: It is well-known that surgical preoperative prophylaxis with broad spectrum antibiotics can select multidrug-resistant Gram-negative bacteria and change the oral microbiome. This prompted us to analyse oral microbiome before and after prophlylactic dose of antibiotics. The main finding of the study is that the prophlylactic application of antibiotics is associated with the colonization of oral cavity with Gram-negative bacteria. Marked diversity of Gram-negative bacteria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“… 2 Antibiotic use is associated with the selection and colonization of multidrug-resistant Gram-negative bacteria (MDR-GNB), which is the most concerning type of antibiotic-resistant bacteria. 1 , 3 It was reported that the prevalence of MDR-GNB carriage varied from 3.64% to 50.62%, depending on the setting, region, and period. 4–6 According to a systematic review, the overall prevalence of antimicrobial-resistant GNB carriage in hospitalized patients was 13.8%, with an 11.0% rate of progression to infection.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Antibiotic use is associated with the selection and colonization of multidrug-resistant Gram-negative bacteria (MDR-GNB), which is the most concerning type of antibiotic-resistant bacteria. 1 , 3 It was reported that the prevalence of MDR-GNB carriage varied from 3.64% to 50.62%, depending on the setting, region, and period. 4–6 According to a systematic review, the overall prevalence of antimicrobial-resistant GNB carriage in hospitalized patients was 13.8%, with an 11.0% rate of progression to infection.…”
Section: Introductionmentioning
confidence: 99%